A Lessons in Pandemic Autonomous Learning Conflicts of Communicative Methods in English Curriculum 2013 along COVID-19 in Indonesia - Giyoto Giyoto; Harun Joko Prayitno; Elen Inderasari; Tri Santoso; Amri Adi Nur Salam; Khoirul Adi Nur Alfisyahri (RIRAI Publisher, 2022)
Communicative competence is the goal of language learning, for which students have to learn language in a real context; and it also becomes the focus of Curriculum 13 in Indonesia. However, due to the COVID-19 pandemic, there are conflicts in realizing communicative competence for the students online. This study aims to identify conflicts faced by the teachers in integrating communicative language teaching method and online platforms used during the pandemic, as the lessons in long distance learnings. This study is qualitative with in-depth interview as the main data collection technique. The respondents of this study cover 137 senior high school teachers. The data is analyzed by identifying the relevant interplays between graduate competences, language learning methods, online platforms used, and conflicts on the teachers and students learning autonomously along pandemic. The findings show that there are conflicts among the teachers and students in implementing online communicative language teaching autonomously, since the method and the used online learning platforms are irrelevant and internet literacy and infrastructure are still poor. There must be comprehensive understanding and skills of the teachers and students in handling autonomous learning digitally along the pandemic including learning outcome, materials, learning methods and process, and testing the outcome. These conflicts bring about lessons of adaptability, collaboration, communication, and resilience, they have learned valuable skills that will serve them well in their future education and careers.